IMPLEMENTASI MICROSOFT WORD SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN KETERAMPILAN SOFTSKILL SISWA SMK IBRAHIMY - Sidra Al Zahro; Alifia Rosa Firdausiah; Zaehol Fatah (Jurnal Padamu Negeri, 2025)
This study aims to analyze the application of Microsoft Word as a learning medium in an effort to improve students' soft skills at SMK Ibrahimy. This activity is designed to equip students with a practical understanding of Microsoft Word features that can support the learning process, such as compiling reports, creating official documents, and organizing information. The Microsoft Word application is very important to use in today's digital era, both for school children to college and even for workers. In addition, the researcher also emphasized the importance of soft skills such as neatness, accuracy, written communication, and the ability to work independently. Through interactive presentation methods and group discussions, students showed high enthusiasm and increased understanding of the application of Microsoft Word in academic and professional activities. The results of our understanding show that the use of appropriate digital media can be an effective means to strengthen the soft skills of SMK students